Crime-Terror Nexus in South Asia : States, Security and Non-state Actors. - Clarke, Ryan (Taylor & Francis, 2011)
This book examines the crime-terror nexus in South Asia, focusing in particular on the activities of non-state actors that operate out of Pakistan, and challenges the conventional wisdom that the Pakistan Taleban (TTP) and Al-Qaeda are Pakistan's most serious security threats.